IMPACT OF VARIOUS SCIENTIFIC DIMENSIONS IN INDIAN CLASSICAL MUSIC: भारतीय षास्त्रीय संगीत में विभिन्न वैज्ञानिक आयामों का प्रभाव - Banawat, Chetna; Gilotra, Anjali (International Journal of Research -GRANTHAALAYAH, 2015)
The tradition of Indian classical music has been ancient and continuous developing in the world. It is like a tree in which, as a result of the seasonal effect, sometimes the autumn and sometimes the Navakopal kept coming, but the root has remained the same. This long-standing tradition of classical music takes place in the Vedic period itself, but various contemporary changes have changed its condition and direction, resulting in considerable qualitative progress in the field of music. Today’s era is receiving the gift of new innovators of science, with which we are all practically familiar. Our musical arts side could not remain untouched by these new scientific designs. Today, with the development of technology and technology, the music world has got a strong foundation. This technology has proved to be helpful in the preservation, promotion and continuous propagation of classical music etc. Various electronic musical instruments, scientific instruments and information technology have also influenced classical music by providing new possibilities like teaching, listening and collecting of classical music, and playing an important role in promoting its conservation and making special contribution in making it sustainable. Huh. भारतीय शास्त्रीय संगीत की परम्परा विष्व में प्राचीनतम् तथा अनवरत् विकासशील रही है। यह उस वृक्ष की भांति है, जिसमें ऋतुकालीन प्रभाव के फलस्वरूप कभी पतझड़ तो कभी नवकोपल आते रहे, किन्तु मूल यथावत् ही रहा है। शास्त्रीय संगीत की इस सुदीर्घ परम्परा के दर्शन वैदिक काल में ही हो जाते हैं, किन्तु विभिन्न समकालीन परिवर्तनों ने इसकी दशा व दिशा में परिवर्तन ला दिया है, फलतः संगीत के क्षेत्र में काफी गुणात्मक प्रगति हुई है। आज के युग को विज्ञान के नित नवीन आविष्कारों की देन प्राप्त हो रही है, जिससे हम सभी व्यवहारिक रूप से परिचित ही हैं। इन नवीन वैज्ञानिक सर्जनाओं से हमारा सांगीतिक कला पक्ष भी अछूता नहीं रह सका। आज तकनीकी व प्रौद्योगिकी के विकास से संगीत जगत् को सुदृढ़ आधार मिला है। संगीत की आदि शाखा शास्त्रीय संगीत के संरक्षण, संवर्धन एवं निरन्तर प्रचार-प्रसार में यह तकनीकी जगत् सहायक सिद्ध हुआ है। विभिन्न इलेक्ट्राॅनिक सांगीतिक वाद्यों, वैज्ञानिक उपकरणों एवं सूचना प्रौद्योगिकी ने शास्त्रीय संगीत के शिक्षण, श्रवण एवं संग्रहण जैसी नवीन सम्भावनाएं भी प्रदान कर शास्त्रीय संगीत को प्रभावित किया एवं इसके संरक्षण-संवर्धन में अहम् भूमिका निभाते हुए इसे चिरस्थायी बनाने में अपना विशेष योगदान भी दे रहे हैं।